IMPLICATURE IN SLOGANS OF MOBILE PHONE ADVERTISEMENT - Wirda Jannatul Jannah; Melliofatria Melliofatria (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Slogans are a way to promote a product. Every advertiser gives a message to promote the product by using a slogan. The meaning of the slogan was difficult to find. In this thesis, the research just focused on the slogan of a mobile phone advertisement. The purpose of this research is to help and guide the consumer or reader to find the meaning of a slogan. The methodology of this research was qualitative. It took about twenty slogans for mobile phone advertisements on the internet. The data was analyzed using Yule’s theory (1996). The implied meaning of the slogan was to represent the advertiser’s message about their product. The meaning of the slogan promotes the quality or quantity of the product. Based on the findings of the research, all the slogans in mobile phone advertisements were concluded to have conversational implications. Because the meaning was not said directly. The result of this research is that all slogans have an implied meaning. From the analysis, it can be concluded that every slogan contains conversational implications.